Study on application of Adaptive Management (AM) in Education Out Loud (EOL) project implementation in the Horn, Eastern adn Southern Africa (HESA) - ANHRE (Oxfam, 2022)
This study mainly aimed to look at adaptive management in the program cycle (throughout Program Cycle processes, including strategy, project , and activity design and implementation) and to look at the Enabling Conditions: how an organization’s culture, business processes, and res ource allocation support adaptive management. It explores elements of adaptive management that correspond to the objectives of the study as follows: 1) Assess grantees’ level of understanding of adaptive manage ment as a programming approach and a method of risk mitigation Methodo logy. 2) Examine how adaptive management has been applied in EOL proje ct implementation thus far. 3) Explore ways in which an adaptive manag ement approach can be used as a source of learning during project impl ementation. 4) Propose ways in which the application of adaptive manag ement can be improved in EOL project implementation. Objective 1: Asse ss grantees’ level of understanding of adaptive management as a progra mming approach and a method of risk mitigation Methodology: The resear chers asessed whether the EOL program, GMU, and HESA RMU have a cultur e of openness, continuous learning, reflection, and improvement. This assessment looked at actual practices and perceptions of field-based s taff and project officers. In addition, they looked at processes to as sess knowledge management and decision-making process – the ability to distill, share and disseminate knowledge and the awareness among gran tees/ employees of the decision-making process. Summary of findings: U nderstanding of adaptive management as a programming approach among th e selected sample of grantees was linked to continuous learning, the a bility to adjust implementation and inform decision making to reach th e intended objectives based on analysis and assessment of the context and flexibility in management. RMU HESA was perceived to have a cultur e of openness where grantees feel comfortable sharing their opinion an d ideas and is perceived to be receptive to proposed changes to projec ts and encourage grantees to provide feedback. The HESA RMU-Oxfam Denm ark is also seen as an agency that is very “flexible“. Recommendations : Enhance Capacity building on adaptive management tools, particularly for finance and admin teams with a focus on pro-active adaptive manag ement which scans the horizon for opportunities and risks, and it adap ts to take advantage of them. It explicitly plans for experimentation and regular upgrading of the strategies; it considers learning and the reduction of uncertainty and imperfect knowledge as one of the key ob jectives of the management effort. Objective 2: Examine how adaptive m anagement has been applied in EOL project implementation thus far Meth odology: Two elements were assessed : Collaboration and how internal a nd external collaboration of grantees and grant agent, assessing the a bility to collaborate with other departments within the entity, the ab ility to collaborate with learning partners, other grantees, to what e xtent they consult their stakeholders and their ability to build coali tions. In addition, researchers looked at Adaptation and the best prac tices and lessons learned in adopting change in the design, implementa tion, budgeting or monitoring of EOL programs and the process followed to adapt the desired change. Summary of findings: Adaptive management practices are seen to be adapting to context changes, constant learni ng, and flexibility. The management and coordination of EOL program is deemed to be collaborative, adaptive, and understanding of the emergi ng needs of EOL Program implementation. There is a simple process in p lace for grantees to make changes to the program implementation. Most grantees do take the time to pause and reflect on what is going well a nd what could be improved and to share the knowledge gained with their coalition members and regional coalitions. HESA RMU was found to be e ncouraging learning practices through organizing periodic online and o ffline regional learning and reflection workshops. Compared to other d onors, the majority of grantees believe that EOL provided the highest level of flexibility and ability to adapt which is seen to be a necess ity for advocacy work. However, it is important to enforce structure t o tighten the feedback loop between data and action: adaptive manageme nt aims for double learning more than just correcting deviations in pl anned versus actual. Recommendations: Introducing outcome harvesting t ool as one of the mechanisms to capture outcomes, institutionalization of adaptive management further by developing context analysis tools/ regular reviews of TOC. Further use of Scenario planning as a tool to map and plan different scenarios on how change may happen, and to exam ine the program’s role in making future events happen, enforcing struc ture to tighten the feedback loop between data and action. In addition to the introduction of quarterly planning cycles where data and infor mation gathered in the previous quarter can be used to inform the next planning cycle and update the TOC, project design and activity implem entation strategies. Objective 3: To explore ways in which an adaptive management approach can be used as a source of learning during projec t implementation Methodology: The team assessed the grantees’ ability to use evidence to build their pathways for change, their ability to u se learning to inform decision making, the frequency and habit of revi ewing their theory of change, the risks and opportunities through scen ario planning, how they assess the efficiency of their data collection tools and monitoring and evaluation data quality, on whether they hav e a mechanism to monitor unintended outcomes (outcome harvesting) and reflect. Summary of findings: This study revealed that there is a cult ure of collaborating, learning and openness among grantees and HESA RM U. The EOL program has adopted Re-active Adaptive Management that reli es on regular monitoring and reflection activities to detect unpredict ed challenges and, when needed, to adjust planned actions to remain on track to achieve the desired program outcomes. EOL provided learning opportunities, platforms for knowledge sharing and encouraged peer lea rning among grantees. Recommendations: Encouraging further engagement on knowledge sharing hubs and investing in knowledge transfer on adapt ive management and learning to other partners in targeted countries (E OL to become an influencer in this field), encouraging further engagem ent from learning partners to provide mentorship and support during im plementation and continuous learning on adaptive management tools. RIS P and GISP could be further engaged in the monitoring process. Based o n the stated objective, what was assessed and findings, it would also be interesting to enable grantees distill learnings from AM practices and applying that knowledge to improve project implementation. This me ans AM will be expected to go beyond changing implementation strategie s and budgets and document learnings from such changes and apply them to improve the remaining part of the project. Objective 4: Propose way s in which the application of adaptive management can be improved in E OL project implementation Summary of findings: Grantees were able to a rticulate well their understanding of adaptive management but were les s able to provide concrete examples of how adaptive management is impl emented in practice. There is a culture of collaborating, learning and openness among grantees and HESA RMU. The EOL program relies on regul ar monitoring and reflection activities to detect unpredicted challeng es and, when needed, to adjust planned actions to remain on track to a chieve the desired program outcomes. EOL provided learning opportuniti es, platforms for knowledge sharing and encouraged peer learning among grantees. However, it is important to enforce structure to tighten th e feedback loop between data and action and to institutionalize practi cing adaptive management. Recommendations: A roadmap that looks at rev iewing seven steps for improving adaptive management is recommended as a systematic tool to introduce improvement. This roadmap is useful in a multi-organizational, multi-country set-up where efficient design i s needed to align top-down structuring and requirements with bottom-up diversity and divergence. This roadmap of seven steps is introduced b y HIVOS. These 7 steps can come in a different order and it depends on the user to assess which of the seven steps needs to be undertaken. 1 . Annual Review results/ outcome statements: using outcome harvesting to continuously monitor intended/ unintended outcomes (whether positiv e or negative or within the sphere of control (outputs) or within the sphere of influence (outcomes). 2. Learning questions: Learning from t he monitoring data; Learning about the critical Make-or-Break assumpti ons in the Theory of Change; and Developing learning topics/ questions and learning agenda at each level 3. Changes in context: Identifying possible trends and signs about emerging shifts in the environment, fo llowed by analyzing and collective sense-making of possible implicatio ns for the Theory of Change (is there a need to revise intervention st rategies, desired outcomes, pathways, assumptions? 4. Theory of change : Reviewing the theory of change was not seen as a frequently recommen ded practice. Constant validation of pathways to change and evidence i n the TOC is important. 5. Capacity assessment and development: What c apacities are available amongst the alliance members and partner organ izations in relation to the (revised) Theory of Change; What would be Capacity Development needs in view of the capacity assessment results? 6. Strategies and interventions: With the outcomes achieved and learn ing so far, what can you say about your interventions and strategies? What worked? Why? Is there a need for adjustment? 7. Annual reflection and Planning Who should take part in the annual planning and reflecti on?